Respuestas

¡La mejor respuesta!
2012-07-08T03:43:39+02:00

\sqrt{2x +14} -\sqrt{x-7} =\sqrt{x+5}

 

(\sqrt{2x +14} -\sqrt{x-7})^2 =(\sqrt{x+5})^2

 

2x + 14 +x -7 -2(\sqrt{2x +14} )(\sqrt{x-7}) =x+5

 

3x + 7 -2(\sqrt{2x +14} )(\sqrt{x-7}) =x+5

 

 -2(\sqrt{2x +14} )(\sqrt{x-7}) =x+5 - 3x - 7

 

 -2(\sqrt{2x +14} )(\sqrt{x-7}) =- 2x - 2

 

 (\sqrt{2x +14} )(\sqrt{x-7}) =-2(x +1) ( \frac{1}{-2} )

 

 (\sqrt{2x +14} )(\sqrt{x-7}) = x + 1

 

 [(\sqrt{2x +14} )(\sqrt{x-7})]^2 =( x + 1 )^2

 

(2x +14) (x-7) =x^2 +2x + 1

 

 2x^2 +14x -14x- 98 =x^2 +2x + 1

 

x^2 -2x -99 = 0

 

x^2 -2x = 99    Aumentamos 1 a ambos lados

 

x^2 -2x +1 = 100

 

(x-1)^2 = 100

 

…  x-1 = 10 

 

x = 11